Потерянное колено этнометодологии - Корбут, Андрей (Социологическое обозрение, 2016)
Fitzgerald R., Housley W. (Eds.) (2015). Advances in Membership Categorisation Analysis. London: Sage. xi, 194 p. ISBN 978-1-4462-7072-1 978-1-4462-7073-8